Stable isotope composition of early Danian sediments from the Atlantic Ocean - Frédéric Quillévéré; Richard D Norris; Dick Kroon; Paul A Wilson (PANGAEA, 2008)
A long-standing question in Paleogene climate concerns the frequency and mechanism of transient greenhouse gas-driven climate shifts (hyperthermals). The discovery of the greenhouse gas-driven Paleocene-Eocene Thermal Maximum (PETM; ~55 Ma) has spawned a search for analogous events in other parts of the Paleogene record. On the basis of high-resolution bulk sediment and foraminiferal stable isotope analyses performed on three lower Danian sections of the Atlantic Ocean, we report the discovery of a possible greenhouse gas-driven climatic event in the earliest Paleogene. This event - that we term the Dan-C2 event - is characterized by a conspicuous double negative excursion in delta13C and delta18O, associated with a double spike in increased clay content and decreased carbonate content. This suggests a double period of transient greenhouse gas-driven warming and dissolution of carbonates on the seafloor analogous to the PETMin the early Paleocene at ~65.2 Ma. However, the shape of the two negative carbon isotope excursions that make up the Dan-C2 event is different from the PETM carbon isotope profile. In the Dan-C2 event, these excursions are fairly symmetrical and each persisted for about ~40 ky and are separated by a short plateau that brings the combined duration to ~100 ky, suggesting a possible orbital control on the event. Because of the absence of a long recovery phase, we interpret the Dan-C2 event to have been associated with a redistribution of carbon that was already in the biosphere. The Dan-C2 event and other early Paleogene hyperthermals such as the short-lived early Eocene ELMO eventmay reflect amplification of a regular cycle in the size and productivity of the marine biosphere and the balance between burial of organic and carbonate carbon.
Supplement to: Quillévéré, F et al. (2008): Transient ocean warming and shifts in carbon reservoirs during the early Danian. Earth and Planetary Science Letters, 265(3-4), 600-615, https://doi.org/10.1016/j.epsl.2007.10.040